The development of the chondrocranium of Pyromelana Orix Orix - Engelbrecht, D. van Z.(Dirk van Zyl) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1956.